Pengaruh Car, Npl, Bopo, Dan Ldr Terhadap Return On Asset (Roa) Pada Perusahaan Sub-Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Lailatus Sa’adah; Sri Wahyuni (Universitas Maritim AMNI Semarang, 2023)
This study aims to determine the effect of CAR, NPL, BOPO, and LDR on ROA in National Private Commercial Bank companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The technique used for sampling is purposive sampling method with data from 5 banking companies. This type of research is quantitative research, namely research presented in the form of numbers and statistics. In determining the accuracy of the model that needs to be done is financial data analysis, then testing some of the classical assumptions that underlie the regression model. The analysis technique used is multiple linear regression analysis.Data analysis and hypothesis testing in this study used Eviews software version 12.0. The results of this study indicate that CAR, NPL, BOPO and LDR partially have a positive effect on ROA. The results of this study also show that CAR, NPL, BOPO and LDR simultaneously have an effect on ROA. The ability of several independent variables to influence the dependent variable is 98.2% and the other 2.8% is influenced by other factors outside of this study.